The Influence of Cadiz in Spanish America:Politics, Government and Constitutionalism - Landavazo, Marco Antonio; Sánchez Andrés, Agustín (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
The Constitution of Cadiz had a significant impact on the Spanish colonies in America and the constitutionalism of the new Latin-American countries. But this impact was uneven. The Constitution of 1812 was prevented from being fully implemented across the continent by the wars of independence and the development of the liberal movement in Spain. However, it did still have a significant impact on the American world, particularly in three areas: political practices, local and provincial institutions and American constitutionalism. In the latter case, the influence extended to regions in which the Constitution had yet to be applied, such as those that today form Chile, Argentina and Venezuela.
Keywords: Constitution of Cádiz; Latin America; Latin America constitutionalism